Do koske . Rage - Skerlić, Slobodan Boba (Monte Royal Pictures Beograd, 1998)
This brutal film, full of violent scenes, is set in Belgrade 1996 and follows the emerging clash between two generations of the Serbian mafia. Kovač is the mafia boss who over the years has secured a luxurious life, even becoming a part of the establishment. Now, he just wants to enjoy his heavenly status, but this becomes impossible when his teenage apprentice kidnaps him and, quickly joined by two friends, drives him to a deserted steel mill. As they put him to horrifying torture, the two contrasting mafia ethics are gradually revealed. Kovač, who climbed slowly through the hierarchy, is prepared to do everything necessary, even to cry, in order to survive. The youngsters, however, are wild, impatient and without any respect. They want everything and they want it now, even if they do not know what it is. In fact, the teenagers act purely on impulse, driven by rage and without a clear agenda of what to do with their hostage. As the night goes on, it becomes clear that their venture will result in senseless bloodshed. This indeed happens in a bloody finale when the police arrive amidst the shootout between the two gangs, with only Kovač leaving the scene alive.